Does Urban Security Modulate Transportation Choices and Travel Behavior of Citizens? A National Study in the Dominican Republic - Alonso, Francisco; Useche, Sergio A.; Faus, Mireia; Esteban, Cristina (Frontiers in Sustainable Cities, 2020)
Introduction: Traditionally, the scientific literature on urban and transportation dynamics addresses many topics, but the security-related outcomes of users remain a pending issue, especially in emerging countries and their cities. Nevertheless, recent evidence suggests that, especially in developing countries, security issues may influence people’s decision-making in the choice of transport means, daily urban-trip patterns and road behaviors of users. Objective: The purpose of this study was to explore the relationships between the perceived security (in both urban environments and public transport systems) and the daily-travel behavior and trip patterns of the Dominican Republic population. Methods: This cross-sectional study, performed in 2019, analyzed data collected from 1,026 inhabitants from different cities of the Dominican Republic (54% females and 46% males), who completed a survey on security issues, travel behaviors and transportation-related habits. Results: The results of this research suggest that demographic factors, such as age, education and city/town size, and the safety perceived in the urban environment play a significant role in the choice of transportation modes, as well as in the participants’ experience as victims of crime-related incidents (either witnessing or suffering crime episodes on public transport or city streets) during urban trips performed over the last five years. Conclusion: Overall, the results of this study suggest that perceived safety, in both urban environments and public transport systems, is a relevant issue affecting the daily transport-related patterns and behavioral choices of the Dominican Republic´s population. The results of this research might contribute to the strengthening of transport security planning, considering factors that are not traditionally kept in mind for policymaking in transportation dynamics.